The Work Place Educational Climate in Gynecological Oncology Fellowships Across Europe. Issue 1 (January 2015) - Piek, Jurgen; Bossart, Michaela; Boor, Klarke; Halaska, Michael; Haidopoulos, Dimitrios; Zapardiel, Ignacio; Grabowski, Jacek; Kesic, Vesna; Cibula, David; Colombo, Nicoletta; Verheijen, Rene; Manchanda, Ranjit
<x xml:space="preserve">Abstract</x> Background A good educational climate/environment in the workplace is essential for developing high-quality medical (sub)specialists. These data are lacking for gynecological oncology training. Objective This study aims to evaluate the educational climate in gynecological oncology training throughout Europe and the factors affecting it. Methods A Web-based anonymous survey sent to ENYGO (European Network of Young Gynecological Oncologists) members/trainees to assess gynecological oncology training. This included sociodemographic information, details regarding training posts, and a 50-item validated Dutch Residency Educational Climate Test (D-RECT) questionnaire with 11 subscales (1–5 Likert scale) to assess the educational climate. The χ2 test was used for evaluating categorical variables, and the Mann-Whitney U (nonparametric) test was used for continuous variables between 2 independent groups. Cronbach α assessed the questionnaire reliability. Multivariable linear regression assessed the effect of variables on D-RECT outcome subscales. Results One hundred nineteen gynecological oncological fellows responded. The D-RECT questionnaire was extremely reliable for assessing the educational environment in gynecological oncology (subscales' Cronbach α, 0.82–0.96). Overall, trainees do not seem to receive adequate/effective constructive feedback during training. The overall educational climate (supervision, coaching/assessment, feedback, teamwork, interconsultant relationships, formal education, role of the tutor, patient handover, and overall consultant's attitude) was significantly better (P = 0.001) in centers providing accredited training in comparison with centers without such accreditation. Multivariable regression indicated the main factors independently associated with a better educational climate were presence of an accredited training post and total years of training. Conclusions This study emphasizes the need for better feedback mechanisms and the importance of accreditation of centers for training in gynecological oncology to ensure training within higher quality clinical learning climates.